Duties And Manner Of Learners In The Perspective Of Hadith - Arini Rahman Asrol; Rahmi Maldini Efendi; Kalayo Hasibuan (Yayasan Rahmat Islamiyah, 2025)
Islamic education views knowledge as a way to bring people closer to Allah SWT. In the hadith perspective, the duties and manners of learners are key elements in the formation of Islamic character. This study examines the guidelines for the duties and manners of learners in the hadith, as well as their relevance in the context of modern education. Using a qualitative approach through literature study, this research reveals that Islamic values such as sincere intentions, respect for teachers, perseverance in learning, and practicing knowledge have an important role in facing the challenges of the industrial revolution 4.0 era. This research contributes to the development of an Islamic education system that is not only based on traditional heritage but also adaptive to modern times. The findings are relevant for educational institutions, educators, and learners in building learning that is effective, ethical, and in accordance with Islamic values.